Exit taxes in the context of double tax treaties: is the individual emigrating from South Africa protected against double taxation? - Moser, Karen (Department of Finance and Tax, 2020)
For some countries, such as South Africa, a change of residence to another jurisdiction is a taxable event and may give rise to taxation of capital gains, based on a deemed disposal, even though there has not been an actual realisation of the capital gain. Such taxation is referred to as ‘exit or departure tax’ or ‘exit charge’. Double taxation of capital gains may arise when the former State of residence applies such an exit tax at the time when the taxpayer ceases to be a tax resident of that State, and when the new State of residence, thereafter, taxes the capital gain at the time of the actual disposal of the asset and realisation of the capital gain. A South African resident individual who emigrates, is therefore exposed to the risk of such double taxation. Double tax treaties following the OECD Model Convention aim at avoiding double taxation and provide distributive rules regarding capital gains in Article 13. This study examines if double tax treaties protect the individual emigrating from South Africa against the application of South Africa’s exit tax. Typical assets considered in the study are shares in a company, held as an investment. The analysis begins with an overview of the applicable rules of the South African Income Tax Act in respect of the capital gains tax levied when a South African resident individual emigrates and ceases to be a resident of South Africa. It then distinguishes between exit taxes in the strict sense (taxation of the accrued value at the time of emigration) and trailing taxes (extended tax jurisdiction, taxing the capital gains at the time of realisation after the emigration). The analysis then concentrates on four subquestions, i.e. (i) whether Art. 13(5) of the OECD Model Convention (2017) applies to exit taxes, (ii) whether Art. 13(5) of the OECD Model precludes the application of an exit tax, (iii) to what extent double tax treaties are able to mitigate the risk of double taxation in the case of exit taxes, and (iv) whether the tax treaty network of South Africa provides any protection against double taxation caused by the application of the South African exit tax. It was concluded that it is generally accepted, with the exception of a minority of authors, that the distributive rule of Art. 13(5) OECD Model includes capital gains arising from a deemed alienation and that that article does not preclude the former State of residence from applying its exit tax at the time when the person is still a resident of that State. However, Art. 13(5) OECD Model does preclude the application of trailing taxes after the person ceases to be a resident. In order to allow the application of trailing taxes, double tax treaties need to explicitly provide for this in a specific clause in the capital gains-article of the tax treaty. The exclusive allocation of taxing rights in art. 13(5) OECD Model in favour of the State of residence does not mitigate the risk of double taxation in the case of exit taxes in the strict sense. In order to avoid double taxation of that portion of the capital gain that already has been subjected to an exit tax in the strict sense, double tax treaties need to include a specific clause in the capital gains-article of the tax treaty, which obliges the new State of residence, when taxing the capital gain at the moment of realisation, to take into account the value that was subjected to the exit tax (step-up in the base cost). South Africa concluded only two treaties which provide for such a step-up in the base cost, one of which has not yet entered into force. This leaves the individual South African resident who emigrates, largely unprotected against double taxation of capital gains at a tax treaty level. It is recommended that South Africa include such specific clauses that provide for a step-up in the base cost in more tax treaties, especially in tax treaties with countries that do not already grant a step-up in terms of their domestic tax laws.